Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12864-022-08775-3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy benchmark of the GeneMind GenoLab M sequencing platform for WGS and WES analysis

Abstract: Background GenoLab M is a recently developed next-generation sequencing (NGS) platform from GeneMind Biosciences. To establish the performance of GenoLab M, we present the first report to benchmark and compare the WGS and WES sequencing data of the GenoLab M sequencer to NovaSeq 6000 and NextSeq 550 platform in various types of analysis. For WGS, thirty-fold sequencing from Illumina NovaSeq platform and processed by GATK pipeline is currently considered as the golden standard. Thus this dataset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first mNGS study to systematically describe clinical HAdV genotypes and perform phylogenetic characterization using the GenoLab M platform. In our previous study, GenoLab M showed comparable performance metrics to WGS and whole-exome sequencing ( Li et al, 2022 ), transcriptomics, and LncRNA ( Liu et al, 2021 ) applications when compared in parallel with the Illumina NovaSeq sequencing platform. In the present retrospective study, we compared the applicability of the GenoLab M platform with that of the NextSeq 550 platform in mNGS.…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, this is the first mNGS study to systematically describe clinical HAdV genotypes and perform phylogenetic characterization using the GenoLab M platform. In our previous study, GenoLab M showed comparable performance metrics to WGS and whole-exome sequencing ( Li et al, 2022 ), transcriptomics, and LncRNA ( Liu et al, 2021 ) applications when compared in parallel with the Illumina NovaSeq sequencing platform. In the present retrospective study, we compared the applicability of the GenoLab M platform with that of the NextSeq 550 platform in mNGS.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, GeneMind Biosciences Company Limited launched a new sequencing instrument (GenoLab M ™) based on their previous work on the GenoCare™ single-molecule sequencer ( Li et al, 2022 ), a promising sequencing platform with high performance and low cost. The GenoLab M sequencer employs SBS and reversible termination approaches, which promise to deliver high-quality sequencing data faster and at lower prices than Illumina’s sequencing instruments.…”
Section: Introductionmentioning
confidence: 99%
“…The GenoLab M now generates 300 GB of sequence data in a single run, costing 6 USD/GB ( Liu et al, 2021 ). The previous study has shown that GenoLab M can achieve results comparable to the Illumina platform in the transcriptome, but there are few relevant studies on WES ( Li et al, 2022 ). In this study, we selected two market-proven platforms with high market share and one newly launched sequencing platform to study the impact of different sequencing platforms on WES results.…”
Section: Introductionmentioning
confidence: 99%
“…In October 2020, GeneMind Biosciences Company Limited (GeneMind) launched a new sequencing instrument (GenoLab M) that is fully compatible with Illumina based libraries and does not require any library conversion [ 11 ]. It was revealed that the GenoLab M is a promising sequencing platform for transcriptomics and long non-coding RNA profiling in animal, plant, and human with comparable performance but a lower cost compared to NovaSeq 6000 (Illumina) [ 11 , 12 ]. However, the performance of the GenoLab M platform in other applications has not yet been tested, for example, for single cell sequencing including spatial transcriptomics.…”
Section: Introductionmentioning
confidence: 99%